Annual Plan 2004-05 West Bengal - Planning Commission (Planning Commission, 2004)
At the moment we are faced with new realities at the national level. Though we are passing through hard times, the installation of the United Progressive Alliance Government at the center has aroused great expectations among the people. The expectations essentially veer around the prospects of new policy formulations for unleashing the productive capacity of the vast masses of the people for economic development in an ambience of great opportunities. The common minimum programme of the GOI has laid special emphasis on the growth of Agriculture & increased investment in the social sectors which are need of the hour. It is expected that Union Government will do its best to fulfill the commitments made in the CMP.
Development and Planning Department Government of West Bengal